Health risks associated with female genital mutilation as express by women of childbearing age in Ilorin South Lga, Kwara State, Nigeria - Ibrahim, Ologele; Onaolapo, Abdulrasaq Qazeem; Usman, Jonathan Sunday; Oluwatoyin, Dabiri-Adewumi Azeezat (Penerbit Universiti Kebangsaan Malaysia, 2022)
Female genital mutilation harms girls and women in many ways and it has no health benefits. Therefore, the study investigated the health risks associated with the female genital mutilation as expressed by women of childbearing age in Ilorin South LGA, Kwara State, Nigeria. The objectives of the study were to determine whether dyspareunia and infertility are health risk associated with female genital mutilation. A descriptive research design of the survey type was adopted for the study. The population of the study comprises women of childbearing age. Two hundred and forty-two respondents were sampled for the study. A validated researcher’s developed questionnaire tested for reliability was used for the study. The data collected analyzed using descriptive statistics of chi-square to test the formulated hypotheses at 0.05 level of significance. The findings indicated that dyspareunia and infertility are significant health risks associated with female genital mutilation (Cal. chi-square value > chi-square Table value) at 0.05 alpha level. The study concluded that dyspareunia and infertility are health risk associated with female genital mutilation as express by women of childbearing age in Ilorin South local government area of Kwara State, Nigeria. Evidence generated from the study also suggest implication for the local government authority on the need to conduct enlightenment campaign through mass media on health effects associated with female genital mutilation to enable parents desist from the practice.